Motivation and engagement among Indigenous (Aboriginal Australian) and non-Indigenous students. Issue 4 (21st April 2021) - Martin, Andrew J.; Ginns, Paul; Anderson, Michael; Gibson, Robyn; Bishop, Michelle
Abstract: Among a sample of 472 Indigenous high school students, juxtaposed with 15, 884 non-Indigenous students from the same 54 schools, we investigated variation in motivation and engagement from school to school, and the role of motivation and engagement in predicting various academic outcomes (aspirations, buoyancy, homework completion, and achievement). We found significantly lower mean-levels of motivation and engagement among Indigenous students. Importantly, however, after accounting for age, gender, socio-economic status (SES), and prior achievement, the motivation and engagement differences between Indigenous and non-Indigenous students were markedly reduced. We also found that Indigenous students' positive motivation and engagement (e.g. self-efficacy, mastery orientation, etc.) predicted academic outcomes to a significantly greater extent than their negative motivation and engagement (e.g. anxiety, self-handicapping, etc.) predicted these outcomes. Findings are discussed with particular focus on how they may be helpful in identifying ways to enhance the educational outcomes of Indigenous students.